Judicial Exile and International Judicial Reform: Rethinking the Independence of the Judiciary in a Global Context: Judicial Exile and International Judicial Reform: Rethinking the Independence of the Judiciary in a Global Context - Muzakki, Fauzan; Suganda, Atma; Akkapin, Supaphorn (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
Judicial independence is widely recognized as a cornerstone of justice, yet its realization in the international sphere faces increasing challenges from political pressures and global power asymmetries. This study introduces the concept of judicial alienation to capture the growing disconnection between the normative ideals of international courts and their perceived legitimacy. Using a qualitative design with a normative legal and comparative approach, the research examines primary legal instruments, including the Rome Statute, the UN Charter, and selected judgments of the International Criminal Court (ICC), the International Court of Justice (ICJ), and the World Trade Organization Dispute Settlement Body (WTO DSB), complemented by secondary academic sources. Findings indicate three interrelated patterns: uneven jurisdiction, particularly the ICC’s disproportionate focus on African cases; legitimacy crises, reflected in recurring resistance to ICJ jurisdiction; and the limited scope of reforms, which tend to be procedural rather than structural. Comparative analysis further reveals that while the WTO DSB benefits from broader acceptance through its consensus-based mechanism, the ICC and ICJ remain vulnerable to contestation due to their direct engagement with state sovereignty. The discussion argues that judicial independence should be reconceptualized not only as a normative principle but also as a socio-political practice embedded in global governance. The study contributes theoretically by advancing an interdisciplinary framework and practically by offering reform-oriented recommendations for more inclusive, transparent, and sustainable international judicial institutions.